The effect of long-term thermal exposure at elevated temperatures on microstructures and mechanical properties in centrifugally casted iron-base alloy - Lothongkum, Gobboon; Thaweepornkhasemsukh, Natthasit; Wangyao, Panyawat (Journal of Metals, Materials and Minerals, 2017)
This work has an aim to study and investigate the relationship between high temperature exposure conditions on microstructural evolution and mechanical properties in the iron-based alloy, Fe-30.8 Ni 26.6 Cr alloy, strengthened by carbide precipitation. Two exposure temperatures (900 and 1000°C) with various thermal exposure times are introduced to the as-received alloy. After short-term exposure, it was found that the secondary carbides precipitated early near the primary carbides, which were chromium and niobium/titanium carbide networks. The secondary carbide precipitations were also found in the dendrite cores. The amounts of needle-like carbides and secondary carbide films increased with time and temperature of aging. However, by EDS analysis, the composition of secondary carbides was almost the same as that of primary carbides for 24 hours heating time. However, they continued to change when thermal exposure time increased. It can be summarized that the exposure conditions have effect on shape, size, dispersion and the location of secondary carbides in microstructure and result in the different mechanical properties such as hardness and tensile strength. Under exposure at 900°C, the very fine precipitates of secondary carbide particles located and concentrate in the area close to primary carbide. In case exposure at 1000°C, the coarser secondary carbides dispersed to the cores of dendrites. The needle-like and film carbides were found in heat-treated specimens at both temperatures. The precipitated secondary carbides precipitated after longterm exposure conditions were chromium carbides, which its chemical composition was similar to primary chromium carbide. It could be concluded that the uniform precipitation and dispersion of fine secondary carbides resulted in slightly higher ultimate tensile and yield strengths as well as hardness in the short-term aging. Then both hardness of tensile strength slightly decreased.